Property and application of novel ferrocenyl–azobenzene labeled peptide nucleic acid monomers with the dual stimulus–response characteristics - Liu, Sheng; Wang, Jinqing; Li, Jindu; Chen, Miao; Yang, Shengrong (Inorganica Chimica Acta, 2009)
Excellent reversible photoswitch and redox activities of three novel types of peptide nucleic acid monomers labeled by ferrocenyl–azobenzene units (Fc–Azo–PNAs) are investigated. These results demonstrate that these new photo–redox peptide nucleic acid monomers (PNAs) have great potential in detecting the PNAs and tuning the hybridization with DNA. In this work, three novel types of peptide nucleic acid (PNA) monomers labeled by ferrocenyl–azobenzene units (Fc–Azo–PNAs, 1a, 1b, and 1c) have been synthesized and they all exhibited good reversible photoswitch and redox properties. In the different solvents of ethanol (EtOH) and acetonitrile (ACN), photoisomerization rate constants ( K) of three PNA monomers under UV light irradiation have also been analyzed and compared, discovering that the values of K are closely correlative to their molecular structures. The electrochemical properties of the synthesized PNA monomers are also investigated and the typical redox properties are displayed, demonstrating that they can be regarded as the anchor to be grafted at the end of PNA oligomers for detecting themselves. Finally, according to the analyses of UV–Vis absorption spectrum and differential pulse voltammetry (DPV), the synthesized PNA monomers afford the best detection limit down to 10 −8 M in EtOH. The results also illuminate that PNA monomers with new photo–redox dual stimulus–response characteristics can be realized to detect themselves by the metal complex unit together with azo moiety; moreover, the hybridization with DNA also can be tuned by the isomerization of azo moiety.